A cross-sectional study to assess the factors influencing adherence to directly observed treatment short course among tuberculosis patients in Udupi district - Shylla, Badondor; Narayanan, Prakash; Rao, P. Arathi (Indian Journal of Nursing Sciences, 2024)
Background: Tuberculosis (TB) is a major global health problem and continues to be endemic in certain parts of India. This study was conducted to find the sociodemographic factors and lifestyle-related factors influencing adherence to directly observed treatment short course (DOTS) and the side effects of antitubercular (ATT) drugs among TB patient on DOTS in Udupi district, Karnataka . Materials and Methods: A total of 158 TB-registered patients taking DOTS treatment in Udupi district were recruited using a convenience sampling technique. Morisky Medication Adherence Scale was adopted to assess the adherence level of treatment. Results: About 59.5% of the respondents were having adherence and 40.5% had no adherence to the treatment. Around 26% were alcoholic. Majority of them (86.7%) experienced at least one of the side effects of the ATT drugs. On multivariate analysis, primary education (P = 0.047), pre-university and above (P = 0.025), daily wage workers (P = 0.013), salaried persons (P = 0.015), and traveling cost (P = 0.016) were associated with DOTS adherence. However, predisposing factors such as addictions and the side effects of the ATT drugs did not show any significant association. Conclusion: The greater proportion of the TB patients was adhering to DOTS. Factors such as education, employment status, and traveling cost had a significant association with DOTS adherence. Factors such as discrimination and side effects of ATT were barriers to DOTS adherence.